Field Evaluation of Ragweed Pollen Samplers - Ogden, E. C.; Raynor, G. S. (Journal of Allergy, 1960)
Our experiments have shown that pollen capture by the standard Durham sampler is determined by several factors, in addition to the concentration of pollen in the air. Aerodynamic factors are responsible for the greater collecting ability of the slide when its long axis is placed parallel to the air flow. Orientation of the slide with respect to wind direction may result in a 5 to 1 difference in catch between adjacent slides. It was also found that the amount of pollen captured is a function of the amount of air passing over the slide as well as the concentration of pollen in the air. Thus, an increase of 3 to 4 m.p.h. in the wind speed may give more than a 50 per cent increase in the pollen captured. Since wind speed normally increases with height, elevation of the sampler above the ground determines the wind speed to which the slide is exposed and affects the count. Tests of a filter sampler showed that this device was also affected by wind speed but in an opposite manner, since efficiency in capturing particles in the pollen size range decreases with increasing wind speed. Improvements in the standard sampling technique might include vane orientation of the slide sampler and measurement of the air flow which could be used to correct the count, or the use of round or square slides with similar correction of wind speed. Work is continuing on the development and evaluation of other sampling devices.
Keywords: biology